2017
DOI: 10.1093/hmg/ddx026
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of five novel susceptibility loci for Systemic Lupus Erythematosus (SLE) and integrated network analysis of 82 SLE susceptibility loci

Abstract: We recently identified ten novel SLE susceptibility loci in Asians and uncovered several additional suggestive loci requiring further validation. This study aimed to replicate five of these suggestive loci in a Han Chinese cohort from Hong Kong, followed by meta-analysis (11,656 cases and 23,968 controls) on previously reported Asian and European populations, and to perform bioinformatic analyses on all 82 reported SLE loci to identify shared regulatory signatures. We performed a battery of analyses for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 70 publications
5
38
0
Order By: Relevance
“…These include ATG5 , CDKN1B , DRAM1, CLEC16A , and ATG16L2 . These data strongly supported the notion that autophagy plays an important role in the genetic etiology of SLE . Combining with further follow‐up studies, several variants locating in other autophagy‐related genes were observed to be associated with susceptibility to SLE, including ATG7 , IRGM , LRRK2 , MAP1LC3B, MTMR3 , and APOL1 (Table ) .…”
Section: Genetic Susceptibility Studiessupporting
confidence: 76%
“…These include ATG5 , CDKN1B , DRAM1, CLEC16A , and ATG16L2 . These data strongly supported the notion that autophagy plays an important role in the genetic etiology of SLE . Combining with further follow‐up studies, several variants locating in other autophagy‐related genes were observed to be associated with susceptibility to SLE, including ATG7 , IRGM , LRRK2 , MAP1LC3B, MTMR3 , and APOL1 (Table ) .…”
Section: Genetic Susceptibility Studiessupporting
confidence: 76%
“…Genetic associations between autophagy gene variants were pronounced in Asian populations, as most autophagy genetic associations could be replicated in our previous studies . However, few of these genetic associations were reported in Caucasians or Africans, suggesting genetic heterogeneity and that the autophagy gene has a major impact in Asian populations .…”
Section: Discussionsupporting
confidence: 61%
“…Genetic data derived from GWAS and follow‐up studies indicated variants in genes related to autophagy, including ATG5 , ATG7 , IRGM , DRAM1 , CDKN1B , APOL1 , MTMR3 , CLEC16A , LRRK2 , and ATG16L2 , especially in Asian populations . Most of these genetic associations ( ATG5 , ATG7 , IRGM , MTMR3 , LRRK2 , and ATG16L2 ) could be replicated in our previous studies . However, only a few of these genetic associations were reported in Caucasians ( ATG5 , IRGM , and CLEC16A ) or Africans ( APOL1 ).…”
supporting
confidence: 47%
“…Its gene product, also known as Odin, is shown to modulate epidermal growth factor receptor recycling and stability 46 and has recently been implicated in the etiology of systemic lupus erythematosus (SLE). 47 Even if there is a causal genetic factor involved, the strong linkage disequilibrium that exists between neighboring genes makes it difficult to establish with certainty which variant is directly involved in a pathologic biological process 50…”
Section: Discussionmentioning
confidence: 99%
“…and has recently been implicated in the etiology of systemic lupus erythematosus (SLE) 47. A mechanistic explanation or a direct causal role in the development of CV disease is yet to be identified.…”
mentioning
confidence: 99%